Correlation of serum vitamin D level with various aspects of polycystic ovarian syndrome - Meena, Mahendra; Panda, Soumya Ranjan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Women with PCOS usually suffer from metabolic disturbances and IR, which might be associated with vitamin D metabolism. The objectives of this study are to determine the association of Vitamin-D with metabolic and endocrine parameters in PCOS women and to evaluate specific role of Vitamin-D in PCOS and to correlate the serum Vitamin-D level with various demographic, anthropometric, biochemical, metabolic and hormonal parameters in PCOS patient. Methods: This case control study was carried out between July 2014 and June 2016 in the Department of Obstetrics and Gynaecology, IMS, BHU got ethical clearance from the institute. The study involved 192 patients with polycystic ovarian syndrome based on Rotterdam criteria and 200 healthy age matched women as controls. The data analysis was performed with the help of SPSS 16.0 version for windows. Results: When study subjects are compared according to vitamin-D level (sufficiency, insufficiency and deficiency) there was significant difference for BMI (kg/m2), Waist Hip ratio and TRG (mg/dl). Vitamin-D had significant negative correlation with BMI (p=0.000); Waist:Hip ratio (p=0.012); Triglyceride (p=0.022). Conclusions: Our study found an association between the high prevalence of obesity and metabolic dysfunction in women with PCOS, and vitamin-D deficiency could be secondary to obesity in such patients. Thus, vitamin-D deficiency cannot be considered as an independent factor through the development of metabolic disorders in PCOS patients.